Design of parallel link mobile robot manipulator mechanisms based on function-oriented element base - Strutynskyi, Serhii; Nochnichenko, Igor (Eastern-European Journal of Enterprise Technologies, 2019)
To create effective mobile robot manipulators, a function-oriented element base is proposed. Element base selection is based on the analysis of schematics of mobile robot manipulators. It is substantiated that the effective schematics of manipulators are parallel link mechanisms. A rational structural scheme was adopted as a mechanism having six rods of variable length (hexapod). The schemes of mobile robot manipulators with different numbers and types of combined rod supports are considered. It is proved that the same type of element base in the form of spherical hinges can be used to implement a variety of schemes. Different embodiments of schematics of manipulators designed on the proposed function-oriented element base are considered. The basic requirements for the element base of mobile robot manipulators are defined. It is shown that the requirements are provided by the function-oriented element base on the basis of different hydrostatic or aerostatic hinges. A series of variants of schematics and design solutions of regulated spherical hydrostatic and aerostatic hinges are proposed. The hydrostatic spherical hinge, which includes an accurate ceramic (boron carbide) ball has high precision characteristics. Technological approbation of this schematic is conducted by manufacturing a production prototype. The regulated hydrostatic hinge is equipped with a mechatronic system for determining the spatial position of the sphere. This design solution allows you to adjust the position of the hinge sphere within the diametric clearance. The combined aerostatic-hydrostatic support unit aggregated with manipulator drives is proposed. The unit has a jet system for adjusting the support reactions of the aerostatic-hydrostatic supports of the spherical hinge. Technological testing of the developed device is carried out. In order to increase the efficiency of the proposed element base, special algorithms for controlling the position of the spherical manipulator hinges are developed. The algorithms are based on the mathematical modeling of dynamic processes in hinge devices. The algorithms include the implementation of spatial polyharmonic displacements of the sphere with the purposeful selection of the direction of the resulting displacements, which provides the necessary accuracy and speed of the process of adjusting the position of the manipulator.